Suffering measurement instruments in palliative care: protocol for a systematic psychometric review. - Gutiérrez-Sánchez, Daniel; Gómez García, Rafael; López-Medina, Isabel María; Cuesta-Vargas, Antonio (BMJ Open, 2019)
Introduction: The prevention and relief of suffering are regarded as a goal at the end of life; therefore, suffering assessment at the end of life is essential. In this regard, we need instruments that allow us to evaluate this construct for gathering more evidence, as the assessment of suffering is increasingly used in research and the clinical setting. Many measures have been designed to assess this construct, and the selection of the most appropriate instrument is crucial. The aims of this systematic review are to (1) identify the measures assessing suffering in patients with advanced disease and their psychometric properties and (2) evaluate the methodological quality of studies on measurement properties. Methods and analysis: The protocol of this systematic review was developed using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Protocols Guidelines. A systematic psychometric review of measures assessing suffering in patients with advanced disease and their psychometric properties will be carried out according to the COnsensus-based Standards for the selection of health status Measurement INstruments (COSMIN). The search strategy will be performed following the Peer Review of Electronic Search Strategies. Searches will be conducted in Cumulative Index to Nursing and Allied Health Literature, Medline, PsycINFO, Cochrane Library, SciELO, Open Grey, Scopus, Web of Science and COSMIN database of systematic reviews, and it will be limited by time (1980-2018) and language (only literature in English and Spanish). Literature will be evaluated by two independent reviewers according to the COSMIN checklist, and measurement properties data of each study that meet the inclusion criteria will be scored independently by two researchers according to COSMIN quality ratings.
Keywords: Dolor; Tratamiento paliativo; Cuidados terminales; Revisiones sistemáticas (Medicina); palliative care; suffering; systematic review